Peningkatan Literasi Finansial dan Digitalisasi Pemasaran pada Kelompok Tani Hutan Green Lawu Kabupaten Karanganyar: Improving Financial Literacy and Marketing Digitalization in the Green Lawu Forest Farmers Group, Karanganyar Regency - Khairiyakh, Refa'ul; Nurhidayati, Indah; Sutrisno, Joko; Irawan, Evi; Ulfa, Amalia Nadifta; Agustono, Agustono; Fajarningsih, Rhina Uchyani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Green Lawu Forest Farmers Group (KTH) is located in Berjo Village, Ngargoyoso District, Karanganyar Regency. KTH Green Lawu is a group whose members live in the area around the Mangkunagoro I Karanganyar Grand Forest Park. This group cultivates and sells orchids to improve the economy of its members. However, the activities of KTH Green Lawu still face various obstacles in its development, including the low knowledge of members regarding financial management, and not yet having the capacity to expand the market. The community service activity carried out by the RG Natural Resources Economics UNS, namely